My Mother's Ghost - Margaret Buffie (U.S.A Kids Can Press, 1992)
Something frightening is happening at Willow Creek Ranch, where Jess and her parents moved after the death of her brother. Jess is seeing things -- or are they seeing her? Margaret Buffie's ambitious novel delicately intertwines two stories -- one set in 1908, the other in the present -- and explores how Jess deals with her own and her parents' grief.
Keywords: Mystery -- Mystery